Value of Sodium-Glucose Co-Transporter 2 Inhibitor Versus Traditional Medication in Microalbuminuric Diabetic Patients - Hussein, Nahla; Abdelrahman, Fatma; Khedr, Abdelrahman; Aref, Hayam; Halawa, Mohamed R.; ELSharkawy, Magdy (Current Diabetes Reviews, 2021)
Background: Sodium glucose co-transporter 2 inhibitor (SGLT2i) is a new arment in the prevention and treatment of diabetic kidney disease with a potential effect on reducing and preventing Chronic Kidney Disease (CKD) progression. Objective: To evaluate the effect of SGLT2 inhibitor in comparison to traditional medication in diabetic patients with microalbuminuria. Methods: A total of 60 diabetic patients with microalbuminuria were divided into group I, where 30 patients were treated by traditional medications (RAAS blockers) and group II where 30 patients were treated by Dapagliflozin added to the traditional medications. All patients were followed up for 6 months and their Urine Albumin/Creatinine Ratio (UACR) and eGFR changes were monitered. Results: UACR significantly declined after 6 months of treatment in group II with a p-value <0.001. There were no significant eGFR changes between both groups. Systolic blood pressure decreases in both groups, but the decrease was highly significant in group II (pvalue<0.001). Diastolic blood pressure decreases significantly in both groups (p-value<0.001). Also, bodyweight reduced significantly in group II with a p-value<0.001. Conclusion: Dapagliflozin, when added to traditional medications (RAAS Blockers), leads to a significant reduction in microalbuminuria with no significant eGFR changes.
Keywords: dapagliflozin